Ecophysiological Response Against Temperature in Klebsormidium (Streptophyta) Strains Isolated From Biological Soil Crusts of Arctic and Antarctica Indicate Survival During Global Warming - Borchhardt, Nadine; Gründling-Pfaff, Sigrid (Frontiers in Ecology and Evolution, 2020)
Global warming, as global problem, may particularly affect the vegetation of the Polar Regions. Biological soil crusts (BSCs) as pioneer communities perform a variety of important ecological functions under the harsh environmental conditions at high latitudes. The green algal genus Klebsormidium is a common member of BSCs and in the present study, the ecophysiological resilience to temperature stress of 20 strains from Arctic and Antarctica were investigated. All 20 Klebsormidium strains exhibited the capability to grow under a wide temperature range (from 6 to 28 °C) and hence were characterized as psychrotolerant with optimum growth temperatures between 18 °C and 26 °C. Statistical analyses showed no significant differences in optimum growth temperature. However, growth rates at optimal temperatures varied between strains and indicated infraspecific physiological plasticity. Furthermore, correlation with the sampling sites as well as different BSC types were examined but no significance was confirmed. Our results revealed that Polar Klebsormidium strains are able to survive such changing conditions, and even benefit from higher environmental temperatures.